Effect of Integration of Linseed and Vitamin E in Charolaise × Podolica Bulls’ Diet on Fatty Acids Profile, Beef Color and Lipid Stability - Valeria Maria Morittu (MDPI AG, 2021)
Dietary supplementation with oilseeds improves the fatty acid profiles of meat, but results are often inconsistent. This study aimed to assess the effects of dietary linseed and vitamin E supplementation on fatty acid profile, cholesterol content and color stability of beef samples. Dorsal subcutaneous fat samples were subjected to lipid stability assessment. Eighteen young bulls (385 ± 15 kg BW, age 8–9 months) were allocated into three homogeneous groups, each receiving ad libitum wheat straw and concentrate only (CON = 5.5 kg/day), concentrate with linseed (LIN = 80 g/kg, i.e., 440 g/head/day), and concentrate with linseed plus vitamin E (L + E = 80 g/kg, i.e., 440 g/head/day + 2500 IU/head/day of Vitamin E). Group L+E showed significantly lower cholesterol content, lower n-6/n-3 ratio and a higher PUFA percentage compared to the CON group. Meat color was affected by feeding LIN with a decrease in a*, b*, and C* compared to the CON group. The experimental diets increased H° values compared to the CON group. A positive effect of vitamin E in protecting lipids of dorsal subcutaneous depots from oxidation was detected in group L+E compared to group LIN. The supplementation with extruded linseeds in the diet had positive effects on the nutritional profile of the meat. When vitamin E was included, linseed did not alter the color of meat, and the lipid stability of the subcutaneous fat improved.